RETRACTED: Clinical significance of SPOCK2 expression signature for high-grade serous ovarian cancer patients - Jiao, Mi; Sun, Wenbo; Li, Lina; Li, Chunyan; Zhou, Jing; Li, Qian; Duan, Lian (Frontiers in Genetics, 2022)
Background: SPOCK2 is a member of the SPOCK family, a 424-amino acid protein that binds to glycosaminoglycans to form proteoglycans. The purpose of this study was to explore expression profile of SPOCK2, and evaluate prognostic potential and its correlation with immune infiltration in high-grade serous ovarian cancer (HGSOC). Methods: Expression of SPOCK2 mRNA and protein between normal and tumor tissues were analyzed using the Cancer Genome Atlas database (TCGA), Gene Expression Omnibus (GEO), Clinical Proteomic Tumor Analysis Consortium (CPTAC), and the Human Protein Atlas (HPA) databases. Receiver operating characteristic (ROC) curve was used to evaluate diagnostic performance of SPOCK2. Kaplan-Meier method and Cox regression analysis were conducted to assess the effect of SPOCK2 on survival. Nomogram was used to predict the impact of SPOCK2 on prognosis. LinkedOmics were used to find correlated genes and perform functional enrichment analyses. The relationships between SPOCK2 and tumor infiltrating lymphocytes (TILs) were determined by tumor-immune system interaction database (TISIDB) and GSVA package (V1.34.0). Results: SPOCK2 was highly expressed in HGSOC tissue compared to normal tissue at both mRNA (P < 0.001) and protein (P = 0.03) levels. The area under the curve (AUC) is 0.894 (CI: 0.865-0.923). Kaplan-Meier analysis showed that HGSOC patients with high-level SPOCK2 mRNA expression had a worse overall survival (OS) than those with a low expression (HR = 1.45, P = 0.005). Univariate logistic regression analysis found that age, primary therapy outcome, tumor status, tumor residual, and SPOCK2 expression level were significantly associated with OS (P < 0.05). The nomogram model indicated an effective predictive performance of SPOCK2. Kyoto encyclopedia of genes and genomes (KEGG) and gene ontology (GO) term analyses showed that SPOCK2 were mainly involved in regulating extracellular matrix. Immune infiltration analysis showed that SPOCK2 may correlate with abundance of TILs. Conclusion: SPOCK2 has potentials to estimate diagnosis and prognosis for HGSOC and is involved in regulating extracellular matrix and immune cell infiltration.